ASSOCIATION OF SLEEP DURATION AND QUALITY WITH CARDIOVASCULAR RISK FACTORS IN PAKISTANI ADULTS - Dr. Shaima Sultana Memon; Dr. Saif Ali Khan; Dr. Maria Tunio; Dr. Shumaila khan; Dr. Muneeza Lodhi; Dr. Sobia Khan Nabeel (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Introduction In many years, cardiovascular disease (CVDs) have arisen as a main source of bleakness and mortality around the world, including in Pakistan. Objectives The basic aim of the study is to find the association of sleep duration and quality with cardiovascular risk factors in Pakistani adults. Material and methods This prospective observational study was conducted in one of the public hospitals of Karachi from June 2022 to December 2022. Data was collected from 180 patients. Informed consent was obtained from each participant after a detailed explanation of the study’s objectives and procedures. Data was collected from 180 patients. Data collection involved sleep assessment and cardiovascular risk factor evaluation. Sleep parameters, encompassing duration and quality, were assessed through a combination of subjective and objective measures. Participants completed self-report assessments, including the Pittsburgh Sleep Quality Index (PSQI) and sleep diaries. Results Data was collected from 180 patients both male and female. The average age of participants was 45.7 ±8.2 years, with a nearly equal distribution of males (49.4%) and females (50.6%). Participants reported an average nightly sleep duration of 6.7±1.2 hours. Sleep quality, as assessed by the Pittsburgh Sleep Quality Index (PSQI), indicated that 67% of participants had poor sleep quality, with a mean PSQI score of 9.5±3.1. Actigraphy data revealed an average sleep duration of 6.3±1.4 hours, with frequent awakenings observed in 43% of participants. Conclusion It is concluded that our study provides evidence of an association between sleep duration and the risk of coronary heart disease in the Pakistani adult population. Short sleep duration appears to be associated with an increased risk of CHD, emphasizing the significance of adequate and quality sleep as a potentially modifiable risk factor.